Clinical predictors of challenging atrioventricular node ablation procedure for rate control in patients with atrial fibrillation. (15th October 2017) - Polin, Baptiste; Behar, Nathalie; Galand, Vincent; Auffret, Vincent; Behaghel, Albin; Pavin, Dominique; Daubert, Jean-Claude; Mabo, Philippe; Leclercq, Christophe; Martins, Raphael P.
Abstract: Introduction: Atrioventricular node (AVN) ablation is usually a simple procedure but may sometimes be challenging. We aimed at identifying pre-procedural clinical predictors of challenging AVN ablation. Methods: Patients referred for AVN ablation from 2009 to 2015 were retrospectively included. Baseline clinical data, procedural variables and outcomes of AVN ablation were collected. A "challenging procedure" was defined 1) total radiofrequency delivery to get persistent AVN block ≥ 400 s, 2) need for left-sided arterial approach or 3) failure to obtain AVN ablation. Results: 200 patients were included (71 ± 10 years). A total of 37 (18.5%) patients had "challenging" procedures (including 9 failures, 4.5%), while 163 (81.5%) had "non-challenging" ablations. In multivariable analysis, male sex (Odds ratio (OR) = 4.66, 95% confidence interval (CI): 1.74–12.46), body mass index (BMI, OR = 1.08 per 1 kg/m 2, 95%CI 1.01–1.16), operator experience (OR = 0.40, 95%CI 0.17–0.94), and moderate-to-severe tricuspid regurgitation (TR, OR = 3.65, 95%CI 1.63–8.15) were significant predictors of "challenging" ablations. The proportion as a function of number of predictors was analyzed (from 0 to 4, including male sex, operator inexperience, a BMI > 23.5 kg/m 2 and moderate-to-severe TR). There was a gradual increase in the risk of "challenging" procedure with the number of predictors by patient (No predictor: 0%; 1 predictor: 6.3%; 2 predictors: 16.5%; 3 predictors: 32.5%; 4 predictors: 77.8%). Conclusions: Operator experience, male sex, higher BMI and the degree of TR were independent predictors of "challenging" AVN ablation procedure. The risk increases with the number of predictors by patient.